Characteristics of Goat's Milk Yoghurt With The Addition of Pineapple Juice (Ananas comosus (L.) Merr.) - Rahmah, Maulia; Dewi, Yohana Sutiknyawati Kusuma; Maherawati, Maherawati (FoodTech: Jurnal Teknologi Pangan, 2024)
Yoghurt is a dairy product fermented with Lactobacillus bulgaricus and Streptococcus thermophilus bacteria, which are then inoculated until the characteristic acidity, odor, and taste are achieved. Goat's milk is an alternative for making yoghurt due to its better nutritional content compared to cow's milk. The addition of pineapple juice in yoghurt production is believed to improve the physicochemical and sensory properties of the yoghurt. This study aimed to investigate the effect of pineapple juice supplementation and determine the concentration of pineapple juice that results in the best physicochemical and sensory characteristics of goat milk yoghurt. The study used a single-factor Randomized Block Design (RBD) with six treatment levels (0%, 5%, 10%, 15%, 20%, and 25%). The best treatment was 20% pineapple juice, which resulted in an average total dissolved solids of 16.50 ºBrix, pH 4.41, total acidity of 0.60%, vitamin C content of 44.00 mg/100g, antioxidant activity of 72.56%, L* of 30.75, a* of -1.48, and b* of 5.43. The sensory characteristics had average values ranging from 3.50 to 3.93, indicating a preference for the color, aroma, texture, taste, and overall characteristics.